The influence of Digital Stimulus On Halal Trust and Digital Purchase Behavior of Halal Micro, Small, and Medium Enterprises Consumers In Indonesia - Selamat Riadi; Ahmad Ridho Hidayat; Kukuh Tondoyekti (Universitas Islam Negeri Mataram, 2025)
This study examines how digital marketing stimuli influence halal trust and digital purchase behavior in the context of Indonesian halal micro, small, and medium enterprises (MSMEs). Using the Stimulus-Organism-Response (S-O-R) framework, social media exposure, perceived value, and promo attractiveness are modeled as stimuli; halal trust as the organism; and digital purchase behavior as the response. Data were collected through an online survey of 73 Muslim consumers who had purchased halal MSME products via digital platforms and were analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that perceived value is the only significant predictor of halal trust, indicating that fair and credible value perceptions are central to building confidence in product halalness. Social media exposure positively affects digital purchase behavior, while promo attractiveness has a significant but negative effect, suggesting that overly aggressive promotions may signal low quality or higher risk. Halal trust does not significantly influence digital purchase behavior and does not mediate the relationships between digital stimuli and behavioral response. These findings refine the application of the S-O-R model in halal digital markets and highlight the need for halal MSMEs to focus on value creation and careful promotion design when targeting online consumers.